Formação do profissional de cultura: desafios e perspectivas - Cunha, Maria Helena (Políticas Culturais em Revista, 2011)
RESUMO: Este artigo tem como perspectiva discutir o tema da formação profissional no campo da cultura, o que significa refletir, necessariamente, sobre o binômio cultura/educação. A educação entendida como um processo contínuo de aquisição de conhecimentos e como direito de cidadania. De forma mais pontual, abordaremos a formação de gestores culturais, cientes que estamos diante de uma profissão contemporânea e complexa. Dando sequencia à reflexão sobre formação profissional e a democratização cultural, voltamos ao tema da educação sob o viés à distância. No caso do Brasil e a realidade de sua extensão territorial, a aprendizagem virtual torna-se uma oportunidade para ampliar o acesso à educação formal e informal de vários profissionais, inclusive do setor cultural.PALAVRAS-CHAVE: Gestão. Cultura. Educação. Educação a distância. The culture professional formation: challenges and perspectivesABSTRACT: This article is an attempt to discuss the theme of professional accomplishment on the cultural field, which means reflecting under the binomial of education/culture. (Here, the Education is) being understood as a continuous process of acquisition of knowledge and as a right of citizenship. In a more punctual view, we will approach on the management training, certain that we’re facing a contemporary and complex profession. Continuing on the reflection about the professional accomplishment and the cultural democratization, we head back to the education theme under the prism of distance. In the reality of Brazil and its territorial extension, the virtual learning becomes an opportunity to amplify the access to formal and informal education of several professionals, including the ones on the cultural field. KEYWORDS: Management. Culture. Education. Distance education.